L’aménagement du musée Nissim de Camondo et le respect du testament du comte Moïse de Camondo, 1936-2014 - Sylvie Legrand-Rossi; Sophie d’Aigneaux Le Tarnec (In Situ)
The Count Moïse de Camondo (1860-1935) planned to bequeath his house and his collection of eighteenth-century French decorative art to his son, Nissim. But in 1924, after Nissim’s premature death in 1917, the house and its collections were left to the French state, with three restrictive clauses. The changes in the interior decoration of the museum, carried out in 1936, are the subject of the present article.